1988
DOI: 10.3354/meps042171
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of refractory cellulosic carbon derived from Spartina alterniflora by the ribbed mussel Geukensia demissa

Abstract: The ab~lity of the ribbed mussel Geukensia demissa (Dillwyn) to ingest and absorb refractory lignocellulosic carbon was evaluated using 14C-radiotracer techniques. Mussels were maintained in a simulated tidal cycle of 6 h submergence and 6 h exposure and were fed on [14C]lignocellulose during the first submergence period. The mean (f SD) absorption efficiency for 14C was 13.3 + 2.5 % in an experiment performed in January 1985, and 14.2 f 1.6 % in a second experiment conducted in March 1985. Approximately 29 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Large heterotrophs are not efficiently removed by G. demissa and are also insufficiently numerous. It is possible that the removal and assimilation efficiencies for non-living clay-organic floc are sufficiently high to allow a substantial incorporation of non-living carbon; Kreeger et al (1988) estimated that suspended cellulosic detritus could provide as much as 15 '10 of the carbon requirements of Delaware populations of G. demissa during the summer. Our estimate of the relative importance of different particle types is partially dependent on their relative abundances, which may vary seasonally, and should be considered representative only for summer.…”
Section: Discussionmentioning
confidence: 99%
“…Large heterotrophs are not efficiently removed by G. demissa and are also insufficiently numerous. It is possible that the removal and assimilation efficiencies for non-living clay-organic floc are sufficiently high to allow a substantial incorporation of non-living carbon; Kreeger et al (1988) estimated that suspended cellulosic detritus could provide as much as 15 '10 of the carbon requirements of Delaware populations of G. demissa during the summer. Our estimate of the relative importance of different particle types is partially dependent on their relative abundances, which may vary seasonally, and should be considered representative only for summer.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope ratios of mussel tissues indicate that G. dernissa derives a large proportion of its C ultimately from vascular plants Spartina alterniflora (Peterson et al 1986, Peterson & Howarth 1987). However, Kreeger et al (1988Kreeger et al ( , 1990 reported that the mussel's abllity to directly utilize refractory cellulosic detritus derived from S. alterniflora, although greater than that of other bivalve species, could only contribute a minor share of the mussel's annual C demand. Our present results support the hypothesis that ribbed mussels obtain at least some of this vascular plant C via the ingestion and assimilation of microheterotrophic intermediaries.…”
Section: Diet Culturesmentioning
confidence: 99%
“…Since ribbed mussels are able to ingest and assimilate microheterotrophs, we suggest that microheterotrophs could indeed mediate the flow of C from vascular plants to benthic suspension-feeders. This would supplement the ribbed mussel's ability to directly digest refractory lignocellulosic detritus (Kreeger et al 1988(Kreeger et al , 1990.…”
Section: Diet Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Langdon & Newel1 (1990) estimated that refractory cellulosic detritus derived from Spartina alterniflora could only supply 0.7 and 8.6% of the carbon requirements of the oyster Crassostrea virginica and the mussel Geukensia demissa, respectively (see also Kreeger et al 1988, Crosby et al 1989, 1990. Although detritus derived from macroalgae has been shown to be more available to deposit feeders than material derived from vascular plants (Tenore 1977, Tenore & Hanson 1980, evidence for the use of macroalgal detritus by suspension feeders is equivocal.…”
Section: Introductionmentioning
confidence: 99%